38th Fluid Dynamics Conference and Exhibit 2008
DOI: 10.2514/6.2008-4273
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Ground Test of Aerothermal Effects on Spherical Capsule Geometries

Abstract: A review is presented of ground test experiments of a 146-mm spherical capsule model with forebody and aftbody symmetry plane measurements of heating and pressure for a range of enthalpies and Reynolds numbers to obtain a dataset of fundamental validation data for CFD codes and to develop a database for design-of-experiment of future studies. Comparisons with laminar experiments are made using CFD demonstrating the influence of thermochemical non-equilibrium on the aerodynamic and aerothermal character of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 37 publications
(47 reference statements)
1
15
0
Order By: Relevance
“…In Eq. (15), R N represents the radius of curvature of the spherical capsule geometry used in the experiments by MacLean et al [5]. In Eq.…”
Section: A Description Of Deterministic Fay-riddell Correlationmentioning
confidence: 99%
See 2 more Smart Citations
“…In Eq. (15), R N represents the radius of curvature of the spherical capsule geometry used in the experiments by MacLean et al [5]. In Eq.…”
Section: A Description Of Deterministic Fay-riddell Correlationmentioning
confidence: 99%
“…To represent an uncertain variable from each uncertainty source, we consider recombination efficiency and the binary collision integral for N 2 -O interaction. A recent work by MacLean et al [5], which included both experimental and numerical studies on the hypersonic aerodynamic heating of spherical capsule geometries, demonstrated a significant variation of the surface heat flux with different recombination efficiencies (e.g., catalytic wall conditions) and at different freestream velocities. Another study by Bose et al [6] demonstrated the effect of uncertainty in the binarycollision integrals on surface heat flux for a Martian entry problem.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…This smaller capsule is a scaled-down version of the split-sting mount studied in the previous section of this work. The data taken on the forebody of this smaller capsule has been studied extensively by MacLean, et al 19 . The detailed geometry and test conditions for the tests are given there so they will not be repeated here, but the model is shown installed in the facility in Fig 35. All tests were performed at a nominal Mach number near 10 at a range of enthalpies in both air and nitrogen from cold flow up to approximately 15 MJ/kg.…”
Section: Experimental Study On the Effect Of Jet Interaction In Thmentioning
confidence: 99%
“…In contrast, several observations have been previously made in the LENS-I reflected shock tunnel in high-enthalpy reacting air and carbon dioxide test gases where macroscopic discrepancies were clearly visible using this comparison technique. [33,34] The comparison of the measured and predicted surface pressure for all six runs is shown in Fig. 12.…”
Section: Experimental Data Comparisons To Cfdmentioning
confidence: 99%